Smear Layer Removal by 1% Phytic Acid after Root Canal Preparation with Three Different Rotary Systems - Soliman , Ali; Rabie , Mohamed; Hassan, Hayam Y. (Open Access Macedonian Journal of Medical Sciences, 2022)
AIM: This study compared the removal of the smear layer using 1% phytic acid or 17% ethylenediaminetetraacetic acid (EDTA) after root canal instrumentation with SmartTrack X3, Endo*star E, and ProTaper Gold rotary systems using an environmental scanning electron microscope (ESEM). METHODS: Sixty single-rooted unidentified extracted human maxillary anterior teeth were selected. The length of all the roots used was adjusted to 16 mm from the apex. Modified access cavities were done. Roots were equally and randomly allocated to three main groups (n = 20) corresponding to the rotary systems: group A1, SmartTrack X3; group A2, Endo*star E3; and group A3, ProTaper Gold. Each group was divided into two equal subgroups (n = 10), corresponding to the chelating agents applied as a final rinse: subgroup B1, 1% phytic acid, and subgroup B2, 17% EDTA. Roots were split in a buccolingual direction into two equal halves and examined under ESEM in the presence or absence of a smear layer at the cervical, middle, and apical segments. RESULTS: 1% Phytic acid and 17% EDTA recorded no statistically significant for removing the smear layer. For all subgroups, there was a significant difference in smear layer removal and more open dentinal tubules in the cervical segment versus the apical segment. CONCLUSION: In smear layer removal from root canals, 1% phytic acid was effective as 17% EDTA in smear layer removal form root canals after SmartTrack X3, Endo*star E3, or ProTaper Gold rotary systems instrumentation.